1978
DOI: 10.1002/j.1552-4604.1978.tb01606.x
|View full text |Cite
|
Sign up to set email alerts
|

Clobazam Versus Diazepam—A Double‐Blind Study in Anxiety Neurosis

Abstract: Clobazam, a new antianxiety compound, was compared in a double-blind study with diazepam in 40 neurotic outpatients. Twenty-three patients completed the trial under clobazam conditions while 17 patients completed the trial under diazepam conditions. The trial was conducted for a period of four weeks of active drug administration followed by a one-week period of placebo administration. Clobazam was administered in three divided doses of 30 to 40 mg/day, while diazepam was administered in three divided doses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1979
1979
1995
1995

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…This trend also emerged in patients (Doongaji et al, 1979;Salkind et al, 1979;Hill et al, 1981) although these latter studies can be criticized for using only a limited range of psychomotor measures.…”
Section: Introductionmentioning
confidence: 96%
“…This trend also emerged in patients (Doongaji et al, 1979;Salkind et al, 1979;Hill et al, 1981) although these latter studies can be criticized for using only a limited range of psychomotor measures.…”
Section: Introductionmentioning
confidence: 96%
“…(Thomson, 1958;Jick et al, 1966) revealed that nitrazepam was a much more potent hypnotic in comparison with clobazam, whereas the latter's sleepfacilitating effect was somewhat stronger than that of placebo. Kesson et al (1978) (Doongaji et al, 1978;Salkind et al, 1979). These findings are of special importance, because clobazam's main indication is the treatment of disorders in out-patient settings.…”
Section: Psychosomatic Disordersmentioning
confidence: 96%
“…Fine motor control Using a hand steadiness task and a Whipple Tracing Board, Doongaji et al (1979) were able to show improved motor co-ordination following repeated dosing with clobazam 10 mg in a group of anxious patients. Trail making tests (Reitan, 1958) have shown both dexamphetamine 30 mg/kg body weight and psilocybin 0.2 mg/kg impair trail making performance (Duke & Keeler 1968).…”
Section: Gross Body Movementmentioning
confidence: 99%
“…, a concept identification task; Jones, Lewis & Spriggs (1978), a group vigilance task; Bond & Lader (1975), the cancellation of 4's; Jones, Jones, Lewis & Spriggs (1979), category clustering; Aschoff, Becker & Weinert (1975), saccadic eye movements; Gagne & Fleishman (1959), the rudder control test; Fleishman & Hempel (1956), multiple limb co-ordination; Jones (1958), an auditory discrimination test; Hindmarch (1975), the choice reaction time task; Hindmarch (1977a), simulated night time car driving performance; Biehl (1979), actual car driving ability; Wittenborn et al (1979), spontaneous reversals of the Necker cube; Taeuber (1977), two handed cordination; Doongaji, Sheth, Apte, Lakdawala, Khare & Thatte (1979) used Whipple's tracing board and Hindmarch & Clyde (1980a, b), a trigram recognition task.…”
mentioning
confidence: 99%